2022
DOI: 10.3390/molecules27217493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound-Assisted Sodium Bicarbonate Treatment on Aggregation and Conformation of Reduced-Salt Pork Myofibrillar Protein

Abstract: To study the effects of an ultrasound (0, 30, and 60 min) and sodium bicarbonate (0% and 0.2%) combination on the reduced-salt pork myofibrillar protein, the changes in pH, turbidity, aggregation, and conformation were investigated. After the ultrasound-assisted sodium bicarbonate treatment, the pH increased by 0.80 units, the absolute value of Zeta potential, hydrophobic force, and active sulfhydryl group significantly increased (p < 0.05), and the turbidity and particle size significantly decreased (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Sulfhydryl groups are important for maintaining the stability of the spatial conformation of MP, and exposure of sulfhydryl groups can improve the gel structure( Gao et al, 2021 ). Active sulfhydryl groups exposed on the surface of protein molecules are necessary for many protein functions( Kang, Shang, Li, & Ma, 2022 ). Zeta potential is a direct index of protein surface charge and can be used to characterize the stability of protein solution systems( Wang et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sulfhydryl groups are important for maintaining the stability of the spatial conformation of MP, and exposure of sulfhydryl groups can improve the gel structure( Gao et al, 2021 ). Active sulfhydryl groups exposed on the surface of protein molecules are necessary for many protein functions( Kang, Shang, Li, & Ma, 2022 ). Zeta potential is a direct index of protein surface charge and can be used to characterize the stability of protein solution systems( Wang et al, 2024 ).…”
Section: Resultsmentioning
confidence: 99%
“…This would strengthen interparticle electrostatic repulsions, improving dispersion stability and contributing to further self-assembly. This outcome is in line with an earlier study, which demonstrated that the application of ultrasound-assisted sodium bicarbonate increases the absolute ζ-potentials of pork myofibrillar protein suspensions …”
Section: Resultsmentioning
confidence: 99%
“…This outcome is in line with an earlier study, which demonstrated that the application of ultrasound-assisted sodium bicarbonate increases the absolute ζ-potentials of pork myofibrillar protein suspensions. 28 Protein Flexibility Characterization. Protein hydrolase is often used for the detection of slight variations in the protein structure, which would hardly be detected by optical means.…”
Section: Intrinsic Emission Fluorescence Spectroscopy and Surfacementioning
confidence: 99%
“…Ultrasonic treatment is a non-toxic processing technology that has been explored in various edible insects (KingwascharapongChaijan and Karnjanapratum, 2021; Rivero-PinoEspejo-Carpio and Guadix, 2020; Wang et al, 2021). Ultrasonic treatment might unfold the protein structure and reduce particle size so that it contributed to functional properties (Kang et al, 2022). An ultrasound-assisted process on Bombay locusts (Patanga succinta L.) proven to enhance yield and protein recovery, alter hydrophobicity, changes in free α-amino concentration, improve solubility, affect the emulsion activity and stability, affect the isoelectric point and molecular features of protein (KingwascharapongChaijan and Karnjanapratum, 2021).…”
Section: Introductionmentioning
confidence: 99%